Project Based Learning untuk Pembelajaran IPAS Kelas IV SDN 118/II Candi - Randi Paslah; Subhanadri Subhanadri; Iri Hamzah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research sought to enhance both the learning quality and outcomes in the subject of Natural and Social Sciences (IPAS) by applying the Project-Based Learning (PjBL) approach in a fourth-grade classroom at SDN 118/II Candi. The study was driven by low student involvement and unsatisfactory academic results, largely due to the overuse of lecture-style instruction and limited variety in teaching strategies. A Classroom Action Research (CAR) design was used, carried out in two cycles that included the stages of planning, execution, observation, and reflection. The participants in this study were 32 fourth-grade students. Data collection involved observing teacher and student activities, as well as administering assessments to evaluate learning progress. The findings showed notable progress in both classroom engagement and student performance. Teacher involvement rose from 62.50% to 95.83%, while the percentage of students demonstrating a